2020
DOI: 10.1155/2020/8548927
|View full text |Cite
|
Sign up to set email alerts
|

Polycarbonate Microchip Containing CuBTC-Monopol Monolith for Solid-Phase Extraction of Dyes

Abstract: In the present study, preparation of CuBTC-monopol monoliths for use within the microchip solid phase extraction was undertaken through a 20-min UV lamp-assisted polymerization for 2,2-dimethoxy-2-phenyl acetophenone (DMPA), butyl methacrylate (BMA), and ethylene dimethacrylate (EDMA) alongside inclusion of the porogenic solvent system (1-propanol and methanol (1 : 1)). The resultant coating underwent coating using CuBTC nanocrystals in ethanolic solution of ethanolic solution of 1,3,5-benzenetricarboxylic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…In large-scale gas storage, we need adsorption materials with a volume adsorption capacity. In recent years, it has been found that MOFs with certain structures meet the requirements of adsorption materials and possess stable mechanical properties. ,, …”
Section: Applications Of Monolithic Mofsmentioning
confidence: 99%
“…In large-scale gas storage, we need adsorption materials with a volume adsorption capacity. In recent years, it has been found that MOFs with certain structures meet the requirements of adsorption materials and possess stable mechanical properties. ,, …”
Section: Applications Of Monolithic Mofsmentioning
confidence: 99%